SAINS BIOLOGI DALAM TRADISI LOKAL: SOSIALISASI KEPADA MASYARAKAT TELUK DALAM UNTUK PELESTARIAN ALAM BERDASARKAN KEARIFAN BUDAYA - Murnihati Sarumaha (Universitas Nias Raya, 2024)
Nature conservation based on local cultural wisdom is a relevant and effective approach to preserving ecosystem sustainability and strengthening the relationship between communities and the environment. This community service aims to enhance the understanding and participation of local communities in nature conservation efforts by utilizing the cultural wisdom that already exists within the community. Through activities such as socialization, training, and discussions, the community is encouraged to understand the connection between local traditions and the sustainable management of natural resources. The results of these activities show that the community has started to reimplement traditional practices in nature management, such as reforestation with local plants, harvest scheduling, and culture-based waste management systems. Additionally, the active participation of youth and indigenous leaders in these efforts has further strengthened nature conservation based on cultural wisdom. It is expected that this initiative will have a positive impact on the environment and raise public awareness about the importance of preserving nature through the integration of local traditions and scientific knowledge.